Comparison of height of jump in volleyball, handball and basketball players - Krykant, Patryk; Buśko, Krzysztof (Journal of Education, Health and Sport, 2017)
Celem pracy było porównanie wysokości wyskoku w wyskokach z miejsca (CMJ) i z nabiegu (SPJ) u koszykarzy, siatkarzy i piłkarzy ręcznych. W badaniach udział wzięło 15 siatkarzy, 15 koszykarzy i 15 piłkarzy ręcznych. Koszykarze byli istotnie wyżsi od siatkarzy. Siatkarze i piłkarze ręczni nie różnili się pod względem wysokości ciała. Każdy badany wykonał 3 maksymalne wyskoki pionowe z miejsca i trzy z nabiegu. Nie stwierdzono istotnych różnic w wysokości wyskoku w wyskokach z miejsca i nabiegu między siatkarzami, koszykarzami i piłkarzami ręcznymi. Podsumowując, mimo istotnych różnic w wysokości ciała i zasięgu ramion wysokość wyskoku z miejsca i nabiegu nie różnicowała siatkarzy, koszykarzy i piłkarzy ręcznych. Abstract The aim of the study was to compare the height of the jump obtained in CMJ and SPJ jumps made by the basketball, volleyball and handball players. The study involved 15 volleyball players, 15 basketball players and 15 handball players. The basketball players were significantly taller than the volleyball players. Volleyball players and handball players did not differ in body height. Each players performed 3 maximal counter-movement jump (CMJ) and 3 spike jump (SPJ) – a vertical jump which is performed with a 3-4 step run-up before the take-off. There were no significant differences in the height of jump in CMJ and SPJ between the volleyball players, basketball players and handball players. In conclusion, despite the significant differences in body height and arm range, the height of the jump in CMJ and SPJ did not differentiate between volleyball players, basketball players and handball players.